MINIMAX AIMING AT SEVERAL TARGET SETS FOR STAGE BY STAGE VARYING PROPER LINEAR STOCHASTIC SYSTEMS - Gabrielyan, M. S.; Matevosyan, A. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
Problem of rapprochement is considered at $m$ target sets for stage by stage varying stochastic system. Under certain conditions, based on stochastic processes, the extremal strategy is constructed by a method extremal aiming.
Keywords: stochastic system; rapprochement; extremal strategy